2002
DOI: 10.1177/109821400202300403
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of After-School Programs: A Meta-Evaluation of Methodologies and Narrative Synthesis of Findings

Abstract: Funding for after-school programs has increased dramatically, and there has been a corresponding increase in the need for sound evaluations to document the quality and impact of the programs. A comprehensive search for after-school evaluations was completed in order to conduct a meta-evaluation of evaluation methodologies used and to synthesize the findings of the evaluations. Results of the meta-evaluation indicate that the after-school evaluation reports located for the study demonstrated moderate compliance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
2
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 17 publications
1
52
2
1
Order By: Relevance
“…Another frequent critique of after-school studies is selection bias (Fashola, 2002;Hollister, 2003;Little & Harris, 2003;Scott-Little, Hamann, & Jurs, 2002). Studies commonly compare students who participated in the program to those who did not, with the implication being that any diff erences are caused by the program.…”
Section: Reducing Selection Biasmentioning
confidence: 99%
“…Another frequent critique of after-school studies is selection bias (Fashola, 2002;Hollister, 2003;Little & Harris, 2003;Scott-Little, Hamann, & Jurs, 2002). Studies commonly compare students who participated in the program to those who did not, with the implication being that any diff erences are caused by the program.…”
Section: Reducing Selection Biasmentioning
confidence: 99%
“…10 Clearly, dramatic policy and environmental changes are required to increase children's participation in PA. 11 Although many efforts are ongoing to increase PA during school hours, 12 less has been done to test the effectiveness of programs delivered during after-school hours at schools and community recreation facilities. 13 in addition to academic and social benefits, 14,15 organized, structured after-school programs provide a unique opportunity to engage children in a large amount of moderate-to-vigorous PA (MVPA). these programs have access to trained school staff and well-61 CHILDHOOD OBESITY February 2012 maintained facilities while avoiding competition with academic pursuits.…”
Section: Introductionmentioning
confidence: 99%
“…The research indicates that individuals who can overcome such obstacles share common properties of resiliency, such as high self-esteem, positive life attitudes, and high future aspirations (Rouse, Bamaca-Gomez, & Newman, 2001;Siebert, 2005). These individuals achieve resiliency because they had opportunities to develop affirming personal relationships, to learn about the importance of school, and to gain a sense of well-being, among other positive attributes (Scott-Little, Hamann, & Jurs, 2002). Quality afterschool programs that focus on building resiliency in students can provide such opportunities (Brooks, 2006;Cooper, Estes, & Allen, 2004).…”
Section: Building Resiliency: the Afterschool Modelmentioning
confidence: 99%
“…First, they provide students with supervision during a time when they might normally fall prey to deviant or anti-social behaviors-research has revealed that the rates for both juvenile crimes and the victimization of juveniles peak in the afterschool hours (U.S. Department of Education & U.S. Department of Justice, 2000). Secondly, afterschool programs provide experiences that may benefit students' social skills and work habits (Scott-Little, Hamann, & Jurs, 2002;Vandell, Reisner, & Pierce, 2007). Finally, afterschool programs may help to improve academic achievement through tutoring and enrichment activities (Fashola, 2002).…”
Section: Building Resiliency: the Afterschool Modelmentioning
confidence: 99%